A produtividade do trabalho na indústria de transformação no Brasil (1996 a 2013) - Sousa, Rodolfo Silva Viana (2016)
This study aims to analyze labor productivity behavior in the manufacturing industry in Brazil for the years 1996-2013, from data of the Annual Industrial Survey released by the IBGE. To understand what the origins of the debate on labor productivity first discuss what are the conceptual differences according to the thinking of some of the classics called authors, then to present the main contributions on the subject by the neo-classical and the evolutionary thinking, which they were selected as appropriate for the subject of analysis. In the second phase, an industrial policy analysis and concepts through a resumption of the proposals I PND to PBM is made, identifying in each plan, which mechanisms have been suggested that could generate increases in productivity. Finally, we analyze the current theoretical debate on labor productivity behavior in the manufacturing industry. When we review the empirical data, we concluded that there was a decrease in the indicator for the manufacturing industry between 1996 and 2013. The resumption of industrial policies in the early 2000s did not guarantee support investments to cope with the growth in production, so to meet the expansion of industrial production, it was necessary to increase the number of employed persons at higher rates than the value of industrial transformation, resulting in the fall of the indicator searched